6+(3x-29)-(7-2x)=4

Simple and best practice solution for 6+(3x-29)-(7-2x)=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+(3x-29)-(7-2x)=4 equation:


Simplifying
6 + (3x + -29) + -1(7 + -2x) = 4

Reorder the terms:
6 + (-29 + 3x) + -1(7 + -2x) = 4

Remove parenthesis around (-29 + 3x)
6 + -29 + 3x + -1(7 + -2x) = 4
6 + -29 + 3x + (7 * -1 + -2x * -1) = 4
6 + -29 + 3x + (-7 + 2x) = 4

Reorder the terms:
6 + -29 + -7 + 3x + 2x = 4

Combine like terms: 6 + -29 = -23
-23 + -7 + 3x + 2x = 4

Combine like terms: -23 + -7 = -30
-30 + 3x + 2x = 4

Combine like terms: 3x + 2x = 5x
-30 + 5x = 4

Solving
-30 + 5x = 4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '30' to each side of the equation.
-30 + 30 + 5x = 4 + 30

Combine like terms: -30 + 30 = 0
0 + 5x = 4 + 30
5x = 4 + 30

Combine like terms: 4 + 30 = 34
5x = 34

Divide each side by '5'.
x = 6.8

Simplifying
x = 6.8

See similar equations:

| -2b=-18 | | 3w-6(w-6)=4(w-8) | | 12-3q-9q=-12 | | x-7.1=4.7 | | P+8/2=5 | | 7x-8y=-22 | | 9p+5-p=-7 | | 11=x/9 | | -5x-3(5)=0 | | 6j+8-11=0 | | 140=10d | | 5n+n+10=18 | | 9(x+1)-3(x+1)= | | 17d=68 | | 3r+4r-9=-15 | | .33p+7=12-.67p | | 8(2n-4)=(7n+1)+7 | | y-4=-2(x+2) | | 4x^2-36x+3=0 | | 19-k+9k-7= | | 16q=256 | | 9(x+1)=3(x+1) | | x^6/x^8 | | 5f=-3(8-f) | | x+4-3(x+4)=0 | | C=5/9(81) | | 0/8 | | 11m-6+m-1= | | 4x-5(x+3)=6(x+3) | | 10n+2+9-4n= | | 6y-y-7= | | 11d-6d+6= |

Equations solver categories